The observed thermal response of the upper northeastern Arabian Sea to the onset of the summer monsoon During ISMEX-73 - RAO, RR (MAUSAM, 1986)
Time series measurement of upper ocean temperature made during ISMEX-73 at 180 N & 670 E from a stationary USSR ship during the period 29 May –5 June –2 1973 are utillised to descried and to explain the observed thermal response of northeastern Arabian sea to the forcing of summer monsoonal onset with an embedded vortex system prevailed over the northern Arabian sea 6-13june 1973.With the formation and the passage of the onset vortex the mixed layer cooled around 1.70c and deepened by 50 m over a tree week period . The cooling is mostly attributed to heat exchange at the sea surface and vergence compare to the entrainment of colder waters from below .The layer deepening had its largest component from the Ekman convergence resulting sinking in the surface layer. During the observed post onset vortex regime of one week, retreat in the layer depth of 20 m is attributed to the baroclinic modes of alternate up in the baroclinic mode of alternate upwelling and sinking patterns set up in the track of the vortex system.